Sequential MR enhancement pattern in normal pituitary gland and in pituitary adenoma. - Yuh, W T; Fisher, D J; Nguyen, H D; Tali, E T; Gao, F; Simonson, T M; Schlechte, J A (American Journal of Neuroradiology, 1994)
PURPOSE To measure and evaluate the temporal enhancement characteristics of the normal pituitary gland and pituitary adenoma. METHODS Thirty healthy subjects and 10 patients with sellar pituitary adenomas were studied prospectively using dynamic MR imaging with a 5- or 10-sec temporal resolution during a bolus injection of gadolinium. RESULTS Qualitative visual analysis demonstrated a consistent sequential pattern of pituitary enhancement in which the posterior lobe enhanced earlier than the anterior lobe by approximately 35 sec. Quantitative analysis revealed that posterior lobe enhancement occurred 9.8 +/- 1.5 sec (mean +/- SEM) before the anterior lobe in healthy subjects, whereas tumor enhancement occurred significantly before the anterior lobe but only slightly before the posterior lobe in patients with adenomas. CONCLUSION The sequential enhancement pattern of the normal pituitary gland was found to be consistent with its vascular anatomy. In contrast to previous reports, pituitary adenomas were found to enhance earlier than the anterior lobe. These results suggest that pituitary adenomas have a direct arterial blood supply, similar to that of the posterior pituitary lobe.